The impact of service quality on customer’s satisfaction towards MPH Bookstore Giant Senawang, Seremban / Nor Wahidah Kamarusaman - Kamarusaman, Nor Wahidah (2014)
The purpose of this study is to examine customer’s satisfaction levels regarding of service quality in MPH Bookstore Giant Senawang outlets. To satisfying the customer needs is the major goal and objective in any Business-to customer (B2C). Hence, the quality of service need to be improved regarding to increase the company profit. Therefore, this research will be focused on the impact of service quality on the customer’s satisfaction in MPH Bookstore Giant senawang, Seremban. This research will find out the dimensions of service quality that have directly influence the customer satisfaction at MPH Bookstore Giant Senawang. Then, the study has been conducted in MPH Bookstore Giant Senawang, Seremban, Negeri Sembilan. Different background of respondents has been used in this study. Questionnaires are in Bahasa Melayu and English that has been distributed to each customer who comes to MPH Bookstore. The researcher assumes only 100 respondents to distribute the questionnaires. The respondents were asked to answer on the dimension of the service quality in order to determine their level of satisfaction towards services provided from MPH Bookstore. Moreover, hypothesis of this study were tested using SPSS tools. The finding with overall result specified that the independent variable and dependent variable were excellent and the study supported the hypothesis of the study and were found to be significant related to purchase intention.